Fall Risk Assessment Using Morse Fall Scale and STRATIFY Fall Scale - sigit harun; Untung Sujianto; Andrew Johan (Public Health Department, Faculty of Health Science University Muhammadiyah Bengkulu, 2022)
Abstract: The purpose of this study was to identify the value of fall risk assessment using Morse fall scale and STRATIFY fall scale, to identify the sensitivity and specificity of Morse fall scale and STRATIFY. Design of this research is a analytic descriptive cross-sectional. Sampling technique used consecutive sampling with the total sample 100 respondent. The analysis used to determine sensitivity and specificity was 2x2 table. The results showed value of Morse fall risk scale using cut off point 45 were 51% high fall risk, 35% moderate fall risk, and 14% low fall risk. The value of STRATIFY’S fall risk scale were 18% high fall risk, 46% moderate fall risk, and 36% low fall risk. Using cut off point 45 on Morse Fall Scale, it’s sensitivity was 80% and it’s specificity was 56,3%. The sensitivity of STRATIFY was 31% and specificity was 91,8%. Conclusion: Morse Fall Scale more sensitive than STRATIFY, however specificity of STRATIFY higher than specificity of Morse Fall Scale.